Work Scheduling for American Mothers, 1990 and 2012. (26th October 2019) - Hepburn, Peter
Abstract: American working conditions have deteriorated over the last 40 years. One commonly-noted change is the rise of nonstandard and unstable work schedules. Such schedules, especially when held by mothers, negatively affect family functioning and the well-being and development of children; they have implications for the intergenerational transmission of disadvantage. This article describes and compares the working schedules—in terms of type, duration, and variability—of American mothers in 1990 and 2012 in an attempt to assess whether nonstandard and unstable schedules are growing more common. Analyses demonstrate that evening work has increased in prevalence for single mothers but not for their partnered peers. Mothers in both single-mother and two-partner households experienced considerably greater within-week schedule variability and higher likelihood of weekend work in 2012 than they did in 1990. These changes resulted from widespread shifts in the nature of work, especially affecting less educated mothers.